Condom effectiveness for prevention of Chlamydia trachomatis infection. Issue 4 (1st August 2005) - Niccolai, L M; Rowhani-Rahbar, A; Jenkins, H; Green, S; Dunne, D W
Abstract : Background/objectives: A growing body of evidence is increasingly demonstrating the effectiveness of condoms for sexually transmitted infection (STI) prevention. The purpose of the present analysis was to provide a disease specific estimate for the effectiveness of condoms in preventing Chlamydia trachomatis infection while controlling for known exposure to infection. Methods: Condom effectiveness for C trachomatis was estimated using a medical record database from a public sexually transmitted disease clinic (n = 1455). Clients were classified as having known exposure to C trachomatis if they presented to the clinic as a contact to an infected partner. Results: Among clients with known exposure, 13.3% of consistent condom users were diagnosed with C trachomatis infection compared to 34.4% of inconsistent condom users (adjusted odds ratio = 0.10; 95% CI: 0.01 to 0.83). Among clients with unknown exposure, there was no observed protective effect of condoms. Conclusions: This study provides further evidence that condoms are effective in preventing C trachomatis infection by reporting a disease specific estimate and restricting analyses to individuals with known exposure.